(3GdeYLe GdeTJed Ydi CSeGA TjhN GdCFeI GdfHds - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG CNQLJ CMGOjK cJH GdSfI ddCFeI GdChd hQJHJgG dGjaVi HGdfGXQ Edi GdSBeI hGdedd s
(3BNQgG (B:s
(3JQLeI jMji Hf GdaVd Hf jMji s
(3GfXQ Qbe (B493 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B286 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs